VD_FINDINFO HC / 2023 / 154 vom 6. März 2023 - VD Tribunal cantonal (2023)
CÉDULE HYPOTHÉCAIRE, PROPRIÉTÉ COMMUNE, CONSORITÉ NÉCESSAIRE, LÉGITIMATION ACTIVE ET PASSIVE | 602 al. 3 CC, 856 CC, 865 CC, 70 al. 1 CPC (CH), 70 al. 2 CPC (CH), 84 CPC (CH)